Analysis of Single-Subject Research Designs in Special Needs Education: Some Examples for Application - Possi, Mwajabu (Papers in Education and Development, 2020)
This paper is a product of a case study conducted through desk research to explore and analyse Single-Subject Research Designs (SSRDs), as applied in special needs education. The aim of the study was to generate a broad understanding of the designs in relation to special needs education and enlighten researchers on the different types of SSRDs used in the area. To realise the aim, dissertations and theses in the School of Education library at the University of Dar es Salaam and various books on SSRDs were reviewed. The paper commences by highlighting the meaning and rationale of SSRDs. It further looks into the types of SSRDs and how they are applied in special needs education. Furthermore, the paper illuminates on both internal and external validity (generalisation) when using the SSRDs and discusses on how SSRDs address the question of social validity. Strengths and weaknesses of the designs are discussed at length in the study. Further, replication of SSRDs for generalisation of data has been well stipulated. It is recommended that single-subject research designs or single-case studies be taught to majors in special needs education in higher education training institutions in Tanzania.